Principles of the New Ecosystem Formation: Multicultural Space - Kharlanov A. S., Strygina S. V., Trubnikova N. V., Chursina K. A., Sitokhova T. E., Khachirov K. A., Kotilko V. V., Ermakov D. N., Vragova E. V., Murzakulov N. A., Yslamov M. M., Shpak A. S., Olivio A., Semeno A. A., Danilchenko S. L., Platonova I. I., Sudakov O. V., Sudakov D. V., Danilchenko S. L., Smirnova S. P. (Principles of the New Ecosystem Formation: Multicultural Space, 2022)
within the framework of this work, a comparison of the problem of optimizing the trajectory of a spacecraft with an ideally controlled engine for two- and three-channel control in the vicinity of a circular orbit is proposed. New approaches are introduced to optimize the trajectories of spacecraft in closed form for two- and three-channel control. The Hill-Clohessy-Wiltshire equations are used to describe the motion of the spacecraft in the vicinity of a circular orbit. To solve the optimal control problem, the maximum principle is used. The results of the trajectory optimization problem for two- and three-channel control are compared. Numerical examples of optimal trajectories with an ideally regulated motor in the vicinity of a circular one are given.
Keywords: космический аппарат; оптимальное управление; уравнения Hill-Clohessy-Wiltshire; круговая орбита; optimal control; Hill-Clohessy-Wiltshire equations; spacecraft; circular orbit